Causes for Pauses During Simulated Pediatric Cardiac Arrest. Issue 8 (August 2017) - Kessler, David Oren; Peterson, Dawn Taylor; Bragg, Alexis; Lin, Yiqun; Zhong, John; Duff, Jonathan; Adler, Mark; Brown, Linda; Bhanji, Farhan; Davidson, Jennifer; Grant, David; Cheng, Adam
Abstract : Objectives: Pauses in cardiopulmonary resuscitation negatively impact clinical outcomes; however, little is known about the contributing factors. The objective of this study is to determine the frequency, duration, and causes for pauses during cardiac arrest. Design: This is a secondary analysis of video data collected from a prospective multicenter trial. Twenty-six simulated pediatric cardiac arrest scenarios each lasting 12 minutes in duration were analyzed by two independent reviewers to document events surrounding each pause in chest compressions. Setting: Ten children's hospitals across Canada, the United, and the United Kingdom. Subjects: Resuscitation teams composed of three healthcare providers trained in cardiopulmonary resuscitation. Interventions: A simulated pediatric cardiac arrest case in a 5 year old. Measurements and Main Results: The frequency, duration, and associated factors for each pause were recorded. Communication was rated using a four-point scale reflecting the team's shared mental model. Two hundred fifty-six pauses were reviewed with a median of 10 pauses per scenario (interquartile range, 7–12). Median pause duration was 5 seconds (interquartile range, 2–9 s), with 91% chest compression fraction per scenario (interquartile range, 88–94%). Only one task occurred during most pauses (66%). The most common tasks were a change of chest compressors (25%), performing pulse check (24%), and performing rhythm check (15%). Forty-nine (19%) of the pauses lasted greater than 10 seconds and were associated with shock delivery ( p < 0.001), performing rhythm check ( p < 0.001), and performing pulse check ( p < 0.001). When a shared mental model was rated high, pauses were significantly shorter (mean difference, 4.2 s; 95% CI, 1.6–6.8 s; p = 0.002). Conclusions: Pauses in cardiopulmonary resuscitation occurred frequently during simulated pediatric cardiac arrest, with variable duration and underlying causes. A large percentage of pauses were greater than 10 seconds and occurred more frequently than the recommended 2-minute interval. Future efforts should focus on improving team coordination to minimize pause frequency and duration.